Analisis Finite Element Aluminium Alloy 6063-T5 Pada Jig Positioning Untuk Perakitan Rooftop Interior Mobil - Desy Agustin; Abdul Wahid Arohman; Muhamad Agus; Hasan Sudrajat; Solihin Solihin (Universitas Batanghari Jambi, 2023)
Tools in the production process are needed in the production process in order to accelerate and improve the quality of production, especially in the automotive industry. In this study, a jig positioning machine design will be designed which is used when assembly on the roof panel of a car so that it can help areas that are difficult to reach when doing assembly or design on the roof panel of the car. After designing the required design for the car interior roof panel assembly, it is necessary to test the design of the machine so that when the material on the machine ready to be made is already in the safe category. Testing on the machine is carried out using a material with the type of Aluminum Alloy 6035-t5 with the addition of different force factors, namely 34.3N, 39.2N, and 44.1N. The addition of the force factor is based on the maximum load given when doing the roof panel assembly on the car. The test is carried out by performing simulations using CAD Software on the arm of the jig positioning machine which will be the support when applying the load. The simulation carried out will analyze the value of material suitability factors including the value of deformation, strain-stress, and factor of safety on the jig positioning machine. The results of the simulation show that there is a change in the value of the material suitability factor due to the difference in the applied force. The suitability factor of the material on the designed jig positioning arm can accommodate the weight of the load with a maximum force of 44.1N with a maximum displacement value of 1.062e+02 mm, a stress value of 1.087e+08N/m^2, a FOS value of 1.33e+00, and a Strain value of 1 ,19e-03. Based on the simulation results of the suitability factor of the material, the jig positioning arm is within safe limits.